The Use of Web Learning Media and Entrepreneurship Education E-books - Persada, Alif Ringga; Handoko, Hendri (Educational Insights, 2023)
The era of digitalization 4.0 has entered into all fields including education. The need for digitalization learning needs to be familiarized by all circles. The purpose of this study is to determine the effectiveness, response and influence of web learning media and educational e-books on entrepreneurship courses. The research method used is quantitative research with experimental research designs. The population is Tadris Mathematics student VII semester IAIN Sheikh Nurjati Cirebon in the academic year 2019/2020. The sampling technique used was purposive sampling, where students were taking entrepreneurship courses. Analysis of the data used is the z test and regression test and descriptive analysis. Based on the results of research that the application of web media and e- book entrepreneurship is effective in learning entrepreneurship courses in terms of completeness of student learning outcomes. Student responses to web learning media and e-books are quite good. And the influence of web media and e-books by 67.4% on the achievement of learning outcomes in entrepreneurship courses.